Kecerdasan Buatan sebagai Tantangan Kebebasan Berpendapat di Media Sosial - Aipassa, Merle Emanuella (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Artificial intelligence is defined as a collection of intelligent agents that can be accessed through a single press. The capabilities of artificial intelligence have surpassed humans as it is able to collect, store and process data. As a result, humans are no longer the shapers of technology but the other way around. Initially, the presence of artificial intelligence influenced studies in the natural and exact sciences, but it has now expanded to the economic and social aspects of human life. Social media is one of the places where artificial intelligence is implicated. The number of users reaching 4.76 billion by early 2023 is threatened by the ability of artificial intelligence through an algorithm system that can regulate the presentation of content and be hidden, which has an impact on the formation of public opinion and injures the right to freedom of opinion. This research aims to criticize the presence of AI as a challenge in realizing freedom of speech on social media. With the analysis using communicative action theory, it sees that modern society has been dehumanized and alienated so that critical analysis is needed to overcome injustice and social change to be articulated based on the values embraced by society more fairly. The approach used is qualitative with data collection methods through literature studies. The conclusion shows that the use of algorithms has eliminated the authentic position of humans in the face of artificial intelligence